STRATEGI GURU PKN DALAM MENANAMKAN NILAI ANTI BULLYING PADA SISWA KELAS VII C SMP NEGERI 3 PALAKKA - Ulva; Marwah; Rasid Ridha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the strategies employed by Civic Education (PKn) teachers in instilling anti-bullying values among seventh-grade students of class VII C at SMP Negeri 3 Palakka. Bullying remains a recurring issue in school environments and negatively affects students’ character development and psychological well-being; therefore, the role of Civic Education teachers is essential in fostering moral, social, and humanitarian values to create a safe and respectful learning atmosphere. This research applied a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation involving teachers and students directly. Data analysis was conducted in depth to describe the instructional strategies implemented in promoting anti-bullying values. The findings indicate that Civic Education teachers applied contextual learning strategies by integrating anti-bullying content into relevant learning topics, utilizing discussion and case study methods to enhance students’ critical awareness, and building positive emotional relationships to establish an open and inclusive classroom climate. In addition, teachers demonstrated positive behavior as role models through daily interactions at school. These strategies were proven to improve students’ understanding, empathy, and social responsibility in preventing bullying behavior. The study concludes that Civic Education learning strategies contribute not only to students’ cognitive development but also to affective and psychomotor domains in shaping anti-bullying character.